Lecturers' Perceptions of Synchronous and Asynchronous Online Teaching During the Pandemic - Ningsih, Tri Setya; Hasanah Fajaria, Nurul; Aini, Nurul (Universitas Islam Negeri Raden Intan Lampung, 2026)
The COVID-19 pandemic forced the Government of Indonesia, through the Ministry of Education and Culture, to implement new policies for conducting learning activities online. This shift from face-to-face to online teaching. From there, English lecturer should deal with both synchronous (real-time) and asynchronous (independent) teaching methods. These are the two methods used by English lecturers at as-syafi’iyah Islam University in teaching during the pandemic. This qualitative case study investigates the perceptions of English lecturers toward Synchronous and Asynchronous online teaching. Data were collected through in-depth interviews with four English lecturers at As-Syafi’iyah Islam University, complemented by observations and document analysis. The findings highlight several challenges faced by lecturers, such as unstable internet access, difficulties with keeping student engagement, and an increasing demand for access to the internet. Although these challenges, the study also identifies several advantages of each method of teaching, including the adaptability of asynchronous learning and the quick delivery of feedback in synchronous sessions. These findings have significant implications for improving online teaching strategies, indicating that an effective approach which includes both synchronous and asynchronous techniques could better meet the different needs of students and raise the efficacy of online teaching.